017 Microvolt T-wave Alternans (MTWA) testing in "real world" heart failure (HF): a study of prevalence and incremental prognostic value. (16th May 2012) - Jackson, C E; Myles, R C; Tsorlalis, I K; Dalzell, J R; Rocchiccioli, J P; Spooner, R J; Rodgers, J R; Bezlyak, V; Greenlaw, N; Ford, I; Petrie, M C; Cobbe, S M; et al.
Abstract : Background: Ventricular arrhythmias contribute to the high risk of death in heart failure (HF) and can be treated with an implantable cardioverter-defibrillator (ICD). Microvolt T-wave alternans (MTWA) testing examines beat-to-beat fluctuations in the morphology of the T-wave. Alternans is believed to reflect dynamic instability of repolarisation and to be linked, mechanistically, to ventricular arrhythmias. Observational studies in highly selected populations have suggested that MTWA testing may identify individuals likely to benefit from a primary prevention ICD. The aims of this study were to evaluate the applicability of MTWA testing in an unselected cohort of patients recently hospitalised with HF and determine the prevalence and incremental prognostic value of an abnormal test. Methods: Consecutive admissions with confirmed HF (typical clinical findings and BNP>100 pg/ml) were recruited in three hospitals from 1 December 2006 to 12 January 2009. Survivors were invited to attend 1-month post-discharge for MTWA testing (HearTWave II, Cambridge Heart). Results: 648 of 1003 patients recruited returned for MTWA testing (58% males, mean age 70.8 years). 318 patients (49%) were ineligible for MTWA testing due to atrial fibrillation (AF), pacemaker-dependency or inability to exercise. Of the 330 patients who underwent MTWA treadmill testing, 100 (30%) were positive, 78 (24%) were negative and 152 (46%) were indeterminate. Failure to achieve the target heart rate due to chronotropic incompetence, secondary to β-blocker therapy or physical limitations, accounted for 75% of indeterminate tests. 131 deaths occurred during a mean follow-up of 18 months. 23% of ineligible patients died vs 17% of eligible patients. 12%, 20% and 19% of patients with a positive, negative and indeterminate test, respectively, died (p=0.24). MTWA results were analysed in the accepted way of non-negative (positive and indeterminate) and negative, but there was still no difference in mortality between the groups (p=0.39). MTWA showed no incremental prognostic value in a multivariable mortality model. The independent predictors of mortality were: lower body mass index (HR 0.96 [95% CI 0.93 to 0.99], p=0.01), New York Heart Association class III–IV (1.72 [95% CI 1.2 to 2.47], p=0.003), previous myocardial infarction (1.68 [95% CI 1.18 to 2.4], p=0.004), elevated B-type natriuretic peptide concentration (1.36 [95% CI 1.12 to 1.65], p=0.002) and elevated troponin (1.57 [95% CI 1.04 to 2.37], p=0.03). Conclusion: MTWA treadmill-testing was not widely applicable in typical patients with HF and failed to predict mortality risk. At present MTWA cannot be endorsed as a tool for improving risk stratification in HF.